ANALISIS KUALITAS PELAYANAN PUBLIK BERDASARKAN SURVEI KEPUASAN MASYARAKAT (SKM) (Studi Kasus pada Organisasi Perangkat Daerah (OPD), Kecamatan dan Puskesmas se Kabupaten Rembang) - Rosyidi, Syaiko; Damayanti, Damayanti; Liana Dewi, Dian Ayu; Ilhami, Susanti Dwi; Lukiarti, Ming Ming (Universitas YPPI Rembang, 2024)
The Community Satisfaction Survey (CSS) was conducted to determine the quality of public services provided to the people of Rembang Regency. The results of this survey can be used as a basis for formulating policies for the Rembang Regency Government to improve the quality of public services and improvements in the future. The 2023 CSS contains survey results from 58 Regional Apparatus Organizations (RAO) and Public Service Units (PSU) within the Rembang Regency Government with 5310 respondents using a multi-stage random sampling technique.The results of the Community Satisfaction Survey with the Implementation of Public Services in Rembang Regency in 2023 obtained a Community Satisfaction Index value of 83.68 or on a category scale that the quality of public services in Rembang Regency is B (good). This is in line with the Rembang Regency Regional Medium Term Development Plan (RMTDP) for 2021-2026, namely increasing the quality of public services with the Community Satisfaction Index indicator for 2026, namelly 83.5